Noninvasive positive-pressure ventilation in pregnancy to treat acute pulmonary edema induced by tocolytic agents: a case report - Kotaro Takahashi; Koji Nishijima; Masayuki Yamaguchi; Kensuke Matsumoto; Shunya Sugai; Takayuki Enomoto (Journal of Medical Case Reports, 2021)
Abstract Background We report a case of pulmonary edema induced by tocolytic agents that was successfully managed with noninvasive positive-pressure ventilation (NPPV) and resulted in extended gestation. Case presentation A 36-year-old Japanese pregnant woman received tocolytic therapy with ritodrine hydrochloride, magnesium sulfate, nifedipine, and betamethasone from 28 weeks of gestation. She developed respiratory failure. and her chest X-ray showed enlarged pulmonary vascular shadows. At 29 weeks and 1 day of gestation, she was diagnosed with pulmonary edema induced by tocolytic agents. Because respiratory failure worsened 2 days after ritodrine hydrochloride and magnesium sulfate were stopped, NPPV was initiated. Her respiratory status improved and she was weaned off of NPPV after 3 days. She underwent cesarean section because of breech presentation at 30 weeks and 0 days of gestation due to initiation of labor pains. Conclusions NPPV can be safely administered in cases of tocolytic agent-induced pulmonary edema during pregnancy.